Long-term effects of chloropicrin fumigation on soil microbe recovery and growth promotion of Panax notoginseng - Wang, Xin; Wang, Qing; Li, Wenjing; Zhang, Daqi; Fang, Wensheng; Li, Yuan; Wang, Qiuxia; Cao, Aocheng; Yan, Dongdong (Frontiers in Microbiology, 2023)
Panax. notoginseng is a precious Chinese medicinal material. Soil fumigation can control soilborne disease and overcome the continuous cropping obstacles of P.notoginseng. However, chloropicrin (CP) fumigation can kill non-target soil microorganisms and reduce microbial diversity. This study mainly focuses on the recovery characteristics of soil microbe after soil fumigation by evaluating the ecological restoration of P.notoginseng soil, its sustained control effect on plant diseases, and its promotion effect on crop growth by focusing on the CP fumigation treatment. This study investigated the soil physicochemical properties, P.notoginseng growth status, and microbial community composition after CP fumigation. The results showed that CP fumigation significantly increased soil available phosphorus (P) to 34.6~101.6 mg/kg and electrical conductivity (EC) by 18.7%~34.1%, respectively. High-throughput gene sequencing showed that soil fumigation with CP altered the relative abundance of Trichoderma, Chaetomium, Proteobacteria, and Chloroflexi in the soil while inhibiting a lot of Fusarium and Phytophthora. The inhibition rate of Phytophthora spp. was still 75.0% in the third year after fumigation. Fumigation with CP enhanced P.notoginseng's survival rate and stimulated plant growth, ensuring P.notoginseng's healthy in the growth period. The impact of fumigation on microbial community assembly and changes in microbial ecological niches were characterized using normalized stochasticity ratio (NST) and Levins' niche breadth index. Stochasticity dominated bacterial community assembly, while the fungal community was initially dominated by stochasticity and later by determinism. Fumigation with CP reduced the ecological niches of both fungi and bacteria. In summary, the decrease in microbial diversity and niche caused by CP fumigation could be recovered over time, and the control of soil pathogens by CP fumigation remained sustainable. Moreover, CP fumigation could overcome continuous cropping obstacles of P.notoginseng and promote the healthy growth of P.notoginseng.